2014
DOI: 10.3727/154427214x13910101597247
|View full text |Cite
|
Sign up to set email alerts
|

Happiness, Satisfaction, and Risk Perception

Abstract: This article examines the relationship between reported levels of happiness, satisfaction, and risk perceptions during holiday experiences. Empirical examinations of this relationship have received limited attention by researchers, yet examining this topic has theoretical and practical value. Specifically, the purpose of our study was to examine perceptions of risk to holiday activities and hazards, levels of hedonic satisfaction and positive emotions, and sense of engagement and meaning in life as three core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Our findings show that pre-travel has a continuing impact on tourists' risk experience, which influences tourist perception of the destination's image and subsequent satisfaction with post-travel risk perception and destination image as two mediators. This study thus provides fresh insights into the mechanism from pre-travel risk perception to satisfaction (Chang, 2010;Filep et al, 2014;Quintal et al, 2010;Sohn et al, 2016;Yüksel & Yüksel, 2007).…”
Section: Theoretical Implicationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Our findings show that pre-travel has a continuing impact on tourists' risk experience, which influences tourist perception of the destination's image and subsequent satisfaction with post-travel risk perception and destination image as two mediators. This study thus provides fresh insights into the mechanism from pre-travel risk perception to satisfaction (Chang, 2010;Filep et al, 2014;Quintal et al, 2010;Sohn et al, 2016;Yüksel & Yüksel, 2007).…”
Section: Theoretical Implicationsmentioning
confidence: 92%
“…For instance, Sohn, Lee, and Yoon (2016) found that the risk perception had a negative impact on destination evaluation, but had no direct impact on satisfaction (Sohn et al, 2016). The study by Filep et al (2014) showed that there was no direct relationship between risk perception and satisfaction. Lo (2012) found that tourist risk perception did not have an impact on either satisfaction or behavioral intentions.…”
Section: Introductionmentioning
confidence: 99%
“…The growing importance of adventure tourism is further evidenced by the facts that over one‐quarter of all trips have an adventure tourism component and that, by the year 2050, this number will increase to over 50% of all trips (Lamoureux, Duverger, & Martin, ). While the growth of adventure tourism has been explained by positive experiences associated with the physical activities in the natural environment (Gyimóthy & Mykletun, ; Cater, ; Buckley, ; Beedie, ; Buckley, ), the perceived risk of an adventure activity often enhances the excitement level, enjoyment and thrill one experiences when participating in the activity ( Gyimóthy & Mykletun, ; Cater, ; Laing & Crouch, ; Filep, Klint, Whitelaw, Dominey‐Howes, & Lacy, ). These positive experiences can influence participants to return to the same place for the same activity, ultimately, leading to the success of adventure tourism (Pizam et al ., ).…”
mentioning
confidence: 99%